Interobserver Agreement in Histopathological Subtyping of Malignant Pleural Mesotheliomas - Mona MLIKA; Faouzi MEZNI (Federation of Turkish Pathology Societies, 2021)
Objective: Many recent studies are pointing out the heterogeneity between pathologists in the classification of malignant pleural mesotheliomas. Besides, they reported the prognostic impact of classifying epithelioid mesotheliomas according to the predominant architectural features and the nuclear grade. The authors assessed the interobserver and the intraobserver agreement of subtyping mesotheliomas between 2 pathologists used to thoracic pathology. Material and Method: The observers reviewed all the slides of the malignant pleural mesotheliomas diagnosed during the period ranging from 2004 to 2017. The Cohen Kappa was performed in order to evaluate the agreement between both observers into classifying mesotheliomas, subtyping and grading epithelioid mesotheliomas. Two rounds of examination were planned with a delay period of one month. After the first round, the reviewers discussed the different difficulties and challenges they faced. All the statistic tests were performed using the SPSS software version 12.0. Results: After the first round, a fair agreement between both observers was reported. After the second round, an improvement of the concordance rate with a good agreement in subtyping epithelioid mesotheliomas was noticed. Concerning the grading of mesotheliomas, the interobserver agreement was poor even after the second round examination. The intraobserver reproducibility of epithelioid mesothelioma subtyping was fair or moderate for both reviewers. The intraobserver agreement was poor concerning the grading of epithelioid mesothelioma. Conclusion: Integrating subtyping and grading of epithelioid mesotheliomas into a new classification necessitates an important training of the pathologists. The architectural features' definitions have to be clarified in order to avoid using own subjective opinions and habits by pathologists.